FOTO COMPANY PROFILE CAFE GYPSY KITCHEN AND BAR - Adi Rizki Ramdhani Prastyo; Anis Raharjo; I Made Bayu Pramana (Lp2mpp Isi Denpasar - Ps. Fotografi, 2022)
Gypsy Kitchen and Bar is a cafe located in the Canggu area, Badung Bali. Gypsy Kitchen and Bar here doesn't have a company profile yet. Therefore, the writer is very interested in doing the final project at Gypsy Kitchen and Bar. In this pandemic condition, many cafes in the Canggu area have closed due to the impact of Covid 19. This gave rise to the idea to keep the Gypsy Kitchen and Bar Cafe afloat even in this pandemic condition. The purpose of the creation of this work is to visualize and find out the Company Profile Photo of Gypsy Kitchen And Bar and find out the supporting factors and obstacles. The benefits of creating this work are that it can add insight to the creator, can add references to institutions, and increase knowledge for the community. The author uses an observation method regarding the process of making Company Profile photos of Gypsy Kitchen And Bar by observing objects related to the making of this Company Profile photo. Then proceed with the shooting process to the location. From the results of the photo shoot, the best photo selection stage was carried out and continued to the next stage until the end of the creation process, namely the exhibition. To visualize a unique and interesting Gypsy Kitchen And Bar Company Profile Photo, the author must make direct observations in order to know the process from beginning to end.